University-enterprise interaction in Brazil: The role of the public research infrastructure - Fernanda De Negri; Luiz Ricardo Mattos Teixeira Cavalcante; Patrick Franco Alves (Institute for Applied Economic Research (ipea), 2015)
This paper discusses the university-enterprise interactions in the Brazilian innovation system by focusing on the characteristics of the public research infrastructure which affects its propensity to interact with the industrial sector. Logistic regressions have been used to identify, in a wide set of explanatory variables, the characteristics of the research infrastructure which increase its probability of supplying technological services to firms. Besides the primary data collected from a survey carried out in a sample of institutions related to the Brazilian Ministry of Science, Technology and Innovation (MCTI), data concerning the scientific and technological production of the researchers affiliated to each laboratory have also been used in the regressions. The choice of the explanatory variables was based in a brief literature review on the role of the research infrastructure in the national innovation systems. Aiming at supporting the discussion of the results of the regressions, this review also included a brief report of the recent interactions between the research infrastructure and the industrial sector in Brazil. The main findings of the logistic regressions are: i) the size of the laboratory (as measured by the number of affiliated researchers) and of the qualification of its research team positively and significantly affects its propensity to interact with the industrial sector; ii) multidisciplinary laboratories tend to interact more with the industrial sector than laboratories focused on a single field of expertise; iii) there seems to be a tradeoff between scientific publications and market oriented research, since the number of papers published by the affiliated researchers is negatively correlated to the probability of supplying technological services to firms.
Keywords: O30; O31; 330; technological infrastructure; technological capabilities; university-enterprise interactions